Microwave-assisted biosynthesis of nano silver and its synergistic antifungal activity against Curvularia lunata - Xiao, Xiuhua; Zheng, Zirui; Yu, Haibing; Huang, Weidong; Ji, Wenchao (Frontiers in Materials, 2023)
It is necessary to explore eco-friendly antimicrobial agents to resolve problems such as pathogen resistance and pesticide residues. In this study, Menthahaplocalyx leaf extract was applied to biosynthesize nano silver using a microwave-assisted method. The detailed properties of the nano silver were systematically revealed by several analytical methods. The antifungal activity of nano silver and synergistic antifungal effects of nano silver conjugated with pesticides against Curvularialunata were determined. Pathogen invasion was significantly inhibited (57.3%) on detached and intravital maize leaves when the concentration of nano silver was 200 μg.mL−1, with an inhibition zone diameter of 12.5 ± 1.18 mm. In addition, a clear synergistic antifungal effect of nano silver conjugated with epoxiconazole was observed at volume ratios of 8:2 and 9:1, while the toxicity ratios were 1.18 and 1.11, respectively. These results not only provide a new avenue for pathogen management, but also enable reduced dosages of antibiotics and pesticides to mitigate or avoid emergence of drug-resistant pathogens.